(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The flipped learning methodology is widely used by the teachers to the students of secondary education to make the learning more interesting and effective. The flipped learning methodology is widely becoming more popular in the study of secondary education as it promotes critical thinking and helps the students to get time for learner-centred activities which includes problem-based learning. Flipped learning methodology of ICT provides various advantages to the teachers as well as students by focusing on active dynamic learning which is quite interesting as compared to traditional learning. Different ICT applications such as software and interactive tools support the flipped learning methodology in secondary education. The relationship between the teachers and the students in secondary education gets much interesting with the flipped learning methodology in ICT. Flipped learning methodology of ICT in secondary education enhances the subject learning by adding a lot of value in the key learning areas. The flipped learning methodology of ICT brings the students together where they can discuss the problems and talk about their work which increases the collaboration among them.